Reaction Mechanism of ZrB2-ZrC Formation in Ni-Zr-B4C System Analyzed by Differential Scanning Calorimetry - Jiaying Xu (MDPI AG, 2021)
The reaction mechanism of ZrB2-ZrC formation in a 30% Ni-Zr-B4C system under argon was revealed by using differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results indicated that the reaction mechanism in the Ni-Zr-B4C system was complex. Initially, NixZry and NixBy intermetallics were formed via solid-state diffusion reactions between Ni, B4C and Zr. Then, the eutectic reaction between Ni2B and Ni4B3 lead to the formation of Ni-B liquid. The free C atoms dissolved into the Ni-B liquid to form a Ni-B-C ternary liquid, and then part of the Zr powder dissolved into the surrounding Ni-B-C ternary liquid to form Ni-Zr-B-C quaternary liquid. Finally, ZrB2 and ZrC formed and precipitated out of the saturated liquid. The eutectic liquid plays an important role during the formation of ZrB2-ZrC.